2016
DOI: 10.1002/hep.28821
|View full text |Cite
|
Sign up to set email alerts
|

Octamer 4/microRNA‐1246 signaling axis drives Wnt/β‐catenin activation in liver cancer stem cells

Abstract: These findings uncover the noncanonical regulation of Wnt/β-catenin in liver CSCs by the Oct4/miR-1246 signaling axis, and also provide a novel diagnostic marker as well as therapeutic intervention for HCC. (Hepatology 2016;64:2062-2076).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
120
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(135 citation statements)
references
References 37 publications
(86 reference statements)
14
120
0
Order By: Relevance
“…For example, miR-183-3p was validated as a potent prognostic marker for lung adenocarcinoma in female nonsmokers[40], and declining expression of let-7e-3p was associated with cell cycle arrest and the inhibition of proliferation of cervical cancer cells[41]. High endogenous and circulating miR-1246 modulated by the direct upstream regulator octamer 4 (Oct4) was shown to be a novel diagnostic marker as well as a tool for therapeutic intervention in hepatocellular carcinoma (HCC) by cooperatively driving Wnt/β-catenin signaling activation[42]. In addition, miRNA-1246 was found to be a target gene of p53 in the progression of various cancers, including cervical, colorectal, esophageal, hepatic, and pancreatic cancers[4345].…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-183-3p was validated as a potent prognostic marker for lung adenocarcinoma in female nonsmokers[40], and declining expression of let-7e-3p was associated with cell cycle arrest and the inhibition of proliferation of cervical cancer cells[41]. High endogenous and circulating miR-1246 modulated by the direct upstream regulator octamer 4 (Oct4) was shown to be a novel diagnostic marker as well as a tool for therapeutic intervention in hepatocellular carcinoma (HCC) by cooperatively driving Wnt/β-catenin signaling activation[42]. In addition, miRNA-1246 was found to be a target gene of p53 in the progression of various cancers, including cervical, colorectal, esophageal, hepatic, and pancreatic cancers[4345].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some miRNAs are considered to be carcinogenic. miR-1246 decreases the expression of AXIN2 and GSK3β by activating the Wnt/β-catenin signaling pathway, which in turn promotes the selfrenewal and metastasis of HCSCs [35]. Studies have shown that miR-155 is up-regulated in tumors and down-regulation of miR-155 can inhibit the formation of CSCs.…”
Section: The Function Of Micrornas In Carcinogenesis Of Hcscsmentioning
confidence: 99%
“…Therefore, the key factors involved in embryonic development may play critical roles in carcinogenesis. Studies have shown that Oct4 is overexpressed in human cancers such as bladder [2], breast [3], cervical cancer [4], oral squamous cell carcinoma [5], hepatocellular carcinoma [6] and lung cancer [7, 8]. In embryonic stem cells, Oct4 has been identified to regulate transcriptions of other transcription factors, chromatin modifiers, long non-coding RNAs (lncRNAs) and microRNAs [9, 10].…”
Section: Introductionmentioning
confidence: 99%